Implementasi Diklat E-Learning Dalam Meningkatkan Kompetensi Pegawai Kantor Bea Cukai Belawan, Sumatera Utara - Samudra Fasific; Zulkarnain Lubis; Nina Siti Salmaniah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The issuance of the Head of the Education and Training Agency of Finance Regulation number PER-2/PP/2019 on E-Learning Guidelines within the Ministry of Finance accommodates the implementation of modern e-learning as a primary tool for human resource development. This regulation provides a legal basis and ensures consistency in planning, experimentation, implementation, responsible personnel (PIC), evaluation, reporting, tutors, duration of implementation, and technological support. This research aims to analyze the implementation of e-learning training and the inhibiting and supporting factors in the Bea and Cukai Belawan Office through a qualitative descriptive method and data collection through interviews. The findings indicate that the implementation of E-Learning Training to enhance the competencies of employees in the Bea and Cukai Belawan Office, North Sumatra, still requires improvement. The main inhibiting factor is the lack of employee commitment, while supporting factors include communication, resources, and bureaucratic structure. Recommendations for improvements are necessary to address the inhibiting factors and strengthen the supporting factors in order to enhance the effectiveness of e-learning training implementation in the office.